Temporal dynamics of stem expansion and contraction in savanna trees: withdrawal and recharge of stored water - Scholz, Fabian Gustavo (2008)
Relationships between diel changes in stem expansion and contraction and discharge and refilling of stem water storage tissues were studied in six dominant Neotropical savanna (Cerrado) tree species from Central Brazil. Two stem tissues were studied, the active xylem or sapwood, and the living tissues located between the cambium and the cork, made up predominantly of parenchyma cells (outer parenchyma). Outer parenchyma and sapwood density ranged from 320 to 410 kg m-3, and from 420 to 620 kg m-3, respectively, depending on the species. The denser sapwood tissues exhibited smaller relative changes in cross-sectional area per unit change in water potential compared to the outer parenchyma. Despite undergoing smaller relative changes in cross-sectional area, the sapwood released about 3.5 times as much stored water for a given change in area as the outer parenchyma. Cross-sectional area decreased earlier in the morning in the outer parenchyma than in the sapwood with lag times up to 30 min for most species. The relatively small lag time between dimensional changes of the two tissues suggested that they were hydraulically well connected with each other. The initial morning increase in basal sap flow lagged about 10 to 130 min behind that of branch sap flow. Species-specific lag times between morning declines in branch and main stem cross-sectional area were a function of relative stem water storage capacity, which ranged from 16 to 31% of total diurnal water loss. Reliance on stored water to temporarily replace transpirational losses is one of the homeostatic mechanisms that constrain the magnitude of leaf water deficits in Cerrado trees.